The impact of a professional development program on EFL teachers' beliefs about corrective feedback. (February 2021) - Ha, Xuan Van; Murray, Jill C.
Abstract: This study investigated the impact of a professional development (PD) program enabling teachers to explore and reflect on their beliefs about oral corrective feedback (CF). It examined whether, how and to what extent those beliefs were influenced by a contextually feasible teacher PD program, consisting of a workshop followed by experiential and reflective activities. Participants were ten EFL teachers from two public high schools in Vietnam. Data were collected over a 14-week period, including recordings of pre- and post-intervention interviews, and three sources of written reflections (journals, self-video-recorded lesson reflections, peer observation reflections). Thematic analysis of the multiple data sources showed some minor changes in the teachers' beliefs regarding CF importance, targets and sources, and some major changes regarding CF types and timing. After the program, the teachers claimed to use a broader range of CF types, especially using more output-prompting CF. They became willing to provide immediate CF in both fluency and accuracy work. This study suggests that PD programs consisting of a workshop supported by appropriate, well-guided experiential and reflective activities can help teachers change CF beliefs to be more aligned with the findings of second language acquisition (SLA) research. Implications for teacher PD programs in EFL contexts are discussed.